Leadership Innovation at Qodratullah Islamic Boarding School: The Role of Buya KH. Husni Thamrin Madani - Mustofa Kamal; Duski Ibrahim; Kemas Badaruddin; Leny Marlina (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This research is based on the charismatic spirit, Buya Husni Thamrin's philosophy in leading or managing the Qodratullah Islamic boarding school in Langkan Village can develop rapidly and develop as it is today. The Islamic boarding school under the leadership of Buya Husni Thamrin has experienced extraordinary innovations that are worthy of being used as a model like other Islamic boarding schools in Banyuasin, therefore, it is necessary to conduct research on the extent of Buya Husni Thamrin's charismatic influence or role in leading and developing the Qodratullah Islamic boarding school in Langkan Village. This research is a type of field research. The research method is a qualitative method, with data collection techniques through observation, interviews and documentation. From the overall results of the study, it shows that Buya KH. M. Husni Thamrin Madani is a pesantren leader who distinguishes himself from kyai in general through a unique combination of traditional kyai charisma with visionary, innovative, dynamic, and adaptive nature. While charisma allows him to lead with conviction and assertiveness, what sets him apart is his visionary ability to look ahead, be innovative in implementing modern educational programs, be dynamic in adapting to changing times, and be adaptive to the surrounding environment. The novelty in this study is that Islamic boarding schools in Banyuasin Regency must innovate and transform as carried out by Buya Husni Thamrin that Islamic boarding schools must keep up with the times. By combining traditional values with modern thinking, Buya Husni Thamrin Madani is able to lead the pesantren in a more progressive way, advance religious education, and meet the needs of the community in facing the challenges of the times.